Cover Feature: Homolytic N−S Bond Cleavage in Vinyl Triflimides Enabled by Triplet–Triplet Energy Transfer (Chem. Eur. J. 53/2022). Issue 53 (17th August 2022) - Strauch, Christina; Schroeder, Sebastian; Grelier, Gwendal; Niggemann, Meike
Abstract : Abracadabra ! Homolytic bond cleavage enabled by visible‐light‐induced triplet–triplet energy transfer makes us think of a thioxanthone wizard who performs her magic when being excited in the spotlight. She transfers the energy with her wand to the vinyl triflimides thus inducing homolytic N−S bond cleavage to reveal radicals. Just like the divided woman, these recombine leading to α‐quaternary‐β‐trifluoromethylated amines. More information can be found in the Research Article by M. Niggemann and co‐workers (DOI: 10.1002/chem.202201830 ).